2012
DOI: 10.7150/ijms.5094
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Anthocyanins on Secretion of Helicobacter pylori CagA and VacA Toxins

Abstract: Anthocyanins have been studied as potential antimicrobial agents against Helicobacter pylori. We investigated whether the biosynthesis and secretion of cytotoxin-associated protein A (CagA) and vacuolating cytotoxin A (VacA) could be suppressed by anthocyanin treatment in vitro. H. pylori reference strain 60190 (CagA+/VacA+) was used in this study to investigate the inhibitory effects of anthocyanins; cyanidin 3-O-glucoside (C3G), peonidin 3-O-glucoside (Peo3G), pelargonidin 3-O-glucoside (Pel3G), and malvidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
4
31
1
Order By: Relevance
“…We found that the levels of both secreted VacA was decreased when bacteria were cultured with C3G starting a 12.5 μM of C3G and this decrease was more pronounced proportionately to increases in C3G concentration (Figure 1A). Consistent with previous results21, the bacterial numbers were unchanged by C3G treatment at all concentrations compared to mock-treated bacteria suggesting that the decrease in secreted VacA was not due to a decrease in bacterial cell numbers (data not shown). The levels of total secreted proteins were similar at all concentrations of C3G used as determined by reactivity to rabbit anti- H. pylori polyclonal antibody showing that the decrease in VacA was specific to C3G treatment (Figure 1A and B).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the levels of both secreted VacA was decreased when bacteria were cultured with C3G starting a 12.5 μM of C3G and this decrease was more pronounced proportionately to increases in C3G concentration (Figure 1A). Consistent with previous results21, the bacterial numbers were unchanged by C3G treatment at all concentrations compared to mock-treated bacteria suggesting that the decrease in secreted VacA was not due to a decrease in bacterial cell numbers (data not shown). The levels of total secreted proteins were similar at all concentrations of C3G used as determined by reactivity to rabbit anti- H. pylori polyclonal antibody showing that the decrease in VacA was specific to C3G treatment (Figure 1A and B).…”
Section: Resultssupporting
confidence: 92%
“…In our previous report we showed that C3G inhibited secA transcription21. SecA is an intracellular protein that facilitates translocation of bacterial proteins out of the bacterial plasma membrane19.…”
Section: Resultsmentioning
confidence: 96%
“…However, C3G and BRE exert different effects on H. pylori . In our previous study, we found that purified C3G did not affect the expression of vacA and cagA but inhibited the secretion of VacA and CagA by downregulating secA expression . However, in the present study, we found that BRE downregulated vacA and cagA transcription and inhibited VacA secretion.…”
Section: Discussioncontrasting
confidence: 80%
“…Five independent cDNA samples were analyzed. Primer sequences and PCR conditions used for amplifying cagA , vacA , secA , and galE have been described previously . Primer sequences and PCR conditions used for amplifying the T4SS components are described in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Only few studies have reported the antimicrobial action of anthocyanins against H. pylori . Kim and others () determined that a dose of 0.045 mg cyanidin‐3‐glucoside/mL (similar or lower than ranges used in the current study: 0.03 to 0.15 mg cyanidin‐3‐glucose equivalents/disk) did not show any effect on H. pylori bacterial number; however, H. pylori virulence factors such as cytotoxin‐associated protein A (CagA) and vacuolating cytotoxin A (VacA) decreased. The pretreatment of human gastric epithelial cell lines with anthocyanins isolated from soybean coat in a range of 0.0125 to 0.05 mg/mL (similar or lower than ranges used in this study) decreased the H. pylori ‐induced inflammation markers such as reactive oxygen species (ROS) and interleukin‐8, and inhibited the H. pylori‐ induced inducible nitric oxide synthases and cyclooxygenase‐2 mRNA expression (Kim and others ).…”
Section: Resultsmentioning
confidence: 52%